Impaired antioxidant HDL function is associated with premature myocardial infarction. (19th June 2015) - Distelmaier, Klaus; Wiesbauer, Franz; Blessberger, Hermann; Oravec, Stanislav; Schrutka, Lore; Binder, Christina; Dostal, Elisabeth; Schillinger, Martin; Wojta, Johann; Lang, Irene M.; Maurer, Gerald; Huber, Kurt; et al.
Abstract Background There is growing evidence that the predictive value of HDL cholesterol levels for cardiovascular risk stratification is limited in patients with coronary artery disease (CAD). HDL function seems to be a more sensitive surrogate of cardiovascular risk estimation than simple serum levels. Therefore, we aimed to assess whether impaired antioxidant HDL function is involved in the development of premature acute myocardial infarction (AMI). Methods In this multicentre case–control study, we compared the antioxidant function of HDL, measured by the HDL inflammatory index (HII), and HDL particle size in 184 patients comprising 92 patients with AMI at a very young age (≤40 years of age) and 92 age‐ and gender‐matched controls. Results Antioxidant capacities of HDL were significantly impaired in the acute phase of AMI (HII of 1·50 [IQR 1·10–1·74] vs. 0·56 [IQR 0·41–0·86] in controls, P < 0·001 as well as in the chronic stable phase 1 year after the event (HII of 0·85 [IQR 0·72‐1·03] vs. 0·56 [IQR 0·41–0·86], P < 0·001) compared to controls. Moreover, HDL function in the stable phase remained significantly associated with premature MI in adjusted logistic regression analysis with an OR of 2·24 per SD increase of HII (95% CI 1·28–3·91; P = 0·005). Analyses of HDL size revealed a significant correlation between all HDL subfractions and HDL function in controls, whereas this correlation was lost for large and intermediate HDL in AMI patients. Conclusion Impaired antioxidant function of HDL is independently associated with the development of premature AMI. The maintenance of HDL function might evolve into a significant therapeutic target, especially in patients with premature CAD.